Biomechanical Behaviour and Biocompatibility of Ureidopyrimidinone-Polycarbonate Electrospun and Polypropylene Meshes in a Hernia Repair in Rabbits - Mori da Cunha, Marina Gabriela M C; Hympanova, Lucie; Rynkevic, Rita; Mes, Tristan; Bosman, Anton W; Deprest, Jan (Materials (Basel, Switzerland), 2019)
Although mesh use has significantly improved the outcomes of hernia and pelvic organ prolapse repair, long-term recurrence rates remain unacceptably high. We aim to determine the in vivo degradation and functional outcome of reconstructed abdominal wall defects, using slowly degradable electrospun ureidopyrimidinone moieties incorporated into a polycarbonate backbone (UPy-PC) implant compared to an ultra-lightweight polypropylene (PP) textile mesh with high pore stability. Twenty four New-Zealand rabbits were implanted with UPy-PC or PP to either reinforce a primary fascial defect repair or to cover (referred to as gap bridging) a full-thickness abdominal wall defect. Explants were harvested at 30, 90 and 180 days. The primary outcome measure was uniaxial tensiometry. Secondary outcomes were the recurrence of herniation, morphometry for musculofascial tissue characteristics, inflammatory response and neovascularization. PP explants compromised physiological abdominal wall compliance from 90 days onwards and UPy-PC from 180 days. UPy-PC meshes induced a more vigorous inflammatory response than PP at all time points. We observed progressively more signs of muscle atrophy and intramuscular fatty infiltration in the entire explant area for both mesh types. UPy-PC implants are replaced by a connective tissue stiff enough to prevent abdominal wall herniation in two-thirds of the gap-bridged full-thickness abdominal wall defects. However, in one-third there was sub-clinical herniation. The novel electrospun material did slightly better than the textile PP yet outcomes were still suboptimal. Further research should investigate what drives muscular atrophy, and whether novel polymers would eventually generate a physiological neotissue and can prevent failure and/or avoid collateral damage.